2020
DOI: 10.1017/s0954579420000917
|View full text |Cite
|
Sign up to set email alerts
|

One size does not fit all: Trajectories of body image development and their predictors in early adolescence

Abstract: Background: Negative body image predicts many adverse outcomes. The current study prospectively examined patterns of body esteem development in early adolescence and identified predictors of developmental subtypes. Methods: 328 girls and 429 boys reported annually across a 4-year period (Mage at baseline = 11.14, SD = 0.35) on body esteem, appearance ideal internalization, perceived sociocultural pressures, appearance comparisons, appearance-related teasing, self-esteem, positive and negative affect, and dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 52 publications
2
15
1
Order By: Relevance
“…Similarly, at first glance, the stability of body image scores in the control group over time may also appear inconsistent with prior longitudinal research investigating singular patterns in body image over time, which has shown body satisfaction typically declines during adolescence [38]. However, we investigated the possibility of multiple developmental trajectories of body esteem within the present control group in a separate study [10]. Consistent with other studies that have also examined multiple trajectories [39,40], we found three developmental subgroups with varying stability in body image over time, which may not appear obvious by examining the mean body image scores for the entire control group presented here.…”
Section: 94contrasting
confidence: 65%
See 1 more Smart Citation
“…Similarly, at first glance, the stability of body image scores in the control group over time may also appear inconsistent with prior longitudinal research investigating singular patterns in body image over time, which has shown body satisfaction typically declines during adolescence [38]. However, we investigated the possibility of multiple developmental trajectories of body esteem within the present control group in a separate study [10]. Consistent with other studies that have also examined multiple trajectories [39,40], we found three developmental subgroups with varying stability in body image over time, which may not appear obvious by examining the mean body image scores for the entire control group presented here.…”
Section: 94contrasting
confidence: 65%
“…A systematic review of classroom-based body image interventions for adolescents identified 3 of 16 interventions produced sustained reductions in body dissatisfaction [7]. Effective interventions addressed internalization of cultural appearance ideals, media literacy, and appearance-related teasing, comparisons, and conversations; all of which have been shown to prospectively predict body dissatisfaction during early adolescence [9,10]. However, there was a lack of consistency in effects across trials on outcomes, and between genders, an overreliance on highly skilled external providers (i.e., psychologists and researchers), and intervention fidelity was rarely assessed.…”
mentioning
confidence: 99%
“…Many adolescents are highly invested in their appearance and are vulnerable to the development of body image concerns [ 8 , 10 ]. Adolescents begin to demonstrate declines in body esteem (i.e., appearance and weight satisfaction) at 13 years of age [ 11 ] and this persists throughout mid-adolescence [ 12 , 13 ]. A high proportion of boys (50%) and girls (74%) at age 14 have been found to want to modify something about their body [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Body image concerns are evident in early adolescence, with concerns remaining stable between the ages of 11 and 17 years, if left untreated (Lacroix et al, 2020). These concerns are a prospective risk factor for low self-esteem, depression, disordered eating, smoking, high-risk drinking, drug use and self-harm (Bornioli et al, 2019(Bornioli et al, , 2020Wichstrøm & von Soest 2016).…”
Section: Present Study Rationale and Aimsmentioning
confidence: 99%